Friend or frenemy? The role of trust in human-machine teaming and lethal autonomous weapons systems. (18th May 2020) - Warren, Aiden; Hillas, Alek
ABSTRACT: This article explores the imprecise boundary between Lethal Autonomous Weapons Systems (LAWS) and Human-Machine Teaming – as a subset of Human-Machine Interaction – and the extent both are emerging as a point of concern (and option) in military and security policy debates. As the development of Human-Machine Teaming relates to artificial intelligence (AI) capabilities there also exists an area of concern pertaining to reliability and confidence, particularly in the heat of battle. Also known as Manned-Unmanned Teaming, Human-Machine Teaming attempts to engender trust and collaborative partnerships with robots and algorithms. Clearly the prospect of LAWS in recent times, or so-called 'killer robots, ' has raised questions relating to the degree such devices can be trusted to select and engage targets without further human intervention. Aside from examining the 'trust factor, ' the article also considers security threats posed by both state and non-state actors and the complicit yet inadvertent role multinational corporations play in such developments where civilian technology is modified for dual-purposes. The effectiveness of government regulation over AI, including whether AI can be 'nationalised' for national security reasons, will also be examined as part of AI non-proliferation.